Clinical significance of donor-specific anti-HLA-DR51/52/53 antibodies for antibody-mediated rejection in kidney transplant recipients - Park, Borae Geum; Park, Younhee; Joo, Dong Jin; Huh, Kyu Ha; Kim, Myoung Soo; Kim, Soon Il; Kim, Yu Seun; Kim, Hyon-Suk (Clinical transplantation and research, 2019)
Background : The presence of donor-specific antibodies (DSAs) to human leukocyte antigen (HLA) increases the risk of antibody-mediated rejection (ABMR) after kidney transplantation (KT). However, the clinical relevance of anti-HLA-DR51/52/53 antibodies remains unclear because of their weak antigen expression. This study evaluated the association between anti- HLA-DR51/52/53 DSAs and ABMR. Methods : We retrospectively reviewed the single-antigen-bead panel reactive antibody (single PRA) results of 130 patients tested between August 1, 2009 and March 6, 2015, based on clinical necessity after allograft KT. Single PRA analysis was performed using Luminex assay kits (Lifecodes LSA class I and II). We reviewed the clinical course and biopsy results of patients with anti-HLA-DR51/52/53 DSAs. Results : Post-KT DSAs were identified in 89 of the 130 patients (68.5%), with 26 of 32 class I DSAs and 63 of 66 class II DSAs being immunodominant DSAs. Thirteen patients had anti-HLA-DR51/52/53 DSAs. Three patients with anti-HLA-DR51/52/53 immunodominant DSAs alone were diagnosed with biopsy-proven ABMR. One patient who developed anti-HLA-DR DSA 13 days after KT showed a rapid increase in anti-HLA-DR51 DSA and had biopsy-proven ABMR. Conclusions: Although the expression of the HLA-DR51/52/53 antigen was weak, anti-HLA-DR51/52/53 DSAs might be correlated with biopsy-proven ABMR. Therefore, anti-HLA-DR51/52/53 DSAs must be evaluated as a cause of ABMR after transplantation.